Pendampingan Kepada Madrasah dalam Mengimplementasikan Proyek Penguatan Profil Pelajar Pancasila - Nirwana, Evi Silva; Wiwinda, Wiwinda (IJOCE: Indonesia Journal of Civic Education, 2023)
This study aims to assist madrasahs in implementing the Pancasila Student Profile Strengthening Project initiated by the Ministry of Education and Culture. This program is conducted through mentoring from lecturers and students of the Islamic Religious Education Study Program to strengthen the understanding and implementation of Pancasila values ​​in the madrasah environment. The activities carried out include socialization, training, mentoring, and evaluation. The results of this program show an increase in the understanding and commitment of madrasahs in instilling Pancasila values ​​in students through various learning and habituation activities. The madrasah atmosphere becomes more conducive and reflects Pancasila values, such as tolerance, justice, and unity. In addition, student participation and enthusiasm in activities related to the Pancasila Student Profile Strengthening Project have also increased. The conclusion from the results of this program shows a significant increase in the understanding and commitment of madrasahs to instilling Pancasila values. Keywords: Implementation, Pancasila Student Profile Strengthening Project